2014
DOI: 10.3892/br.2014.387
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance gene 1 C1236T polymorphism and susceptibility to leukemia: A meta-analysis

Abstract: Abstract. Several studies have investigated the association between multidrug resistance gene (MDR1) C1236T polymorphism and leukemia risk, however, these published studies have yielded conflicting results. Thus, the present study carried out a meta-analysis to provide a more precise estimate of the effect of this polymorphism on the susceptibility to leukemia. The published case-control studies regarding the association between MDR1 C1236T polymorphism and leukemia risk were included following a computerized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…Since P-glycoprotein acts as an efflux pump that protects cells against endogenous and exogenous harmful compounds, especially environmental carcinogens, any MDR 1 SNP might alter the P-glycoprotein expression and protein conformation that subsequently culminated in the development of several cancer types including hematologic malignancy as a result of carcinogens' accumulation in cells [31,32]. Among three common SNPs in MDR 1 , including 3435C > T, 1236C > T, and 2677G > T/A, unlike the 2677G > T/A polymorphism which is a non-synonymous SNP and causes an amino acid substitution, the 3435C > T and 1236C > T polymorphisms are synonymous SNPs, not causing a change in the amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…Since P-glycoprotein acts as an efflux pump that protects cells against endogenous and exogenous harmful compounds, especially environmental carcinogens, any MDR 1 SNP might alter the P-glycoprotein expression and protein conformation that subsequently culminated in the development of several cancer types including hematologic malignancy as a result of carcinogens' accumulation in cells [31,32]. Among three common SNPs in MDR 1 , including 3435C > T, 1236C > T, and 2677G > T/A, unlike the 2677G > T/A polymorphism which is a non-synonymous SNP and causes an amino acid substitution, the 3435C > T and 1236C > T polymorphisms are synonymous SNPs, not causing a change in the amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…Some single nucleotide polymorphism (SNP) studies in MDR1 gene have indicated their effect on gene expression and/or protein function, which might be associated with development of cancers, chemotherapy response, and clinical prognosis in tumor patients [8][9][10]. Among the discovered SNPs, C1236T (Exon 12, rs1128503), C3435T (Exon 26, rs1045642), and G2677T/A (Exon 21, rs2032582) are the most common and mainly focused on polymorphisms in the coding region of MDR1 [11][12][13]. Several studies confirmed these three SNPs might have a major impact on the genetic susceptibility to hematopoietic malignancies, as well as the prognosis [13][14][15].…”
Section: Introductionmentioning
confidence: 98%
“…The scientific literature, as reported by Ma et al ( 2015a , b ) in two meta-analysis indicate no clear association between this polymorphism and risk to ALL. In our study, we found that the rs1045642 ABCB1 SNP (known as 3435C > T) was associated with a risk of ALL occurrence.…”
Section: Discussionmentioning
confidence: 86%